A New Lunar DEM Based on the Calibrated Chang'E-1 Laser Altimeter Data. (19th June 2018) - Huang, Yong; Chang, Shengqi; Qin, Songhe; Li, Peijia; Hu, Xiaogong; Fan, Min
Abstract : To improve the lunar DEM accuracy derived from CE-1 altimeter data, CE-1 laser altimeter data are calibrated in this paper. Orbit accuracy and ranging accuracy are the two most important factors to affect the application of altimeter data in the lunar topography. An empirical method is proposed to calibrate CE-1 altimeter data, using gridded LOLA DEM to correct systematic errors of CE-1 altimeter data, and the systematic bias is about -139.52 m. A new lunar DEM grid model based on calibrated CE-1 altimeter data with the spatial resolution of 0.0625° × 0.0625° is obtained as well as a spherical harmonic model at 1400th order. Furthermore, the DEM accuracy is assessed through the comparison with the nearside landmarks of the Moon, and the results show that the DEM accuracy is improved from 127.3 m to 48.7 m after the calibration of laser altimeter data.